Employee Benefits in India – Impact on Attrition and Organisational Commitment - Saxena, Shantanoo (Digital Repository of Theses - SSBM Geneva, 2024)
The study was undertaken to understand the spend on employee benefits and its impact on employee satisfaction, intent to leave and organizational commitment. The west has a lot of weightages on employee benefits and there are numerous studies done which have established the importance benefits have towards employee attraction and retention. India however is a different market with very different dynamics towards employee benefits. To understand the impact of offering benefits to employees in India I have initiated this study as the perception of benefits is still nascent in India. Employees across India working across multiple industries in both domestic and multinationals were surveyed on the impact of benefits that are provided to them. We were able to take this survey to the workforce in India and we had 115 people responding for the survey. The study demonstrated that employees' intentions to leave the company are not much impacted by their satisfaction with benefits. A complete ranking of different benefits showcased that employee benefits in India though valued is not the prime benefit an employee is seeking and the impact of offering benefit is more on the organizational commitment then on the retention or attraction of the talent. This suggests that workers view benefits through a different lens, and Indian firms should consider creating rewards that better reflect workers increased organizational commitment and make use of additional techniques to better understand turnover problems. CHROs in India should plan their investments appropriately and be aware of this aspect of what Indian employees need today. There should be future studies conducted in this field at a larger scale to understand the impact in different sectors and geographies of India.